Y-4=0.7(x-3.5)

Simple and best practice solution for Y-4=0.7(x-3.5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-4=0.7(x-3.5) equation:


Simplifying
Y + -4 = 0.7(x + -3.5)

Reorder the terms:
-4 + Y = 0.7(x + -3.5)

Reorder the terms:
-4 + Y = 0.7(-3.5 + x)
-4 + Y = (-3.5 * 0.7 + x * 0.7)
-4 + Y = (-2.45 + 0.7x)

Solving
-4 + Y = -2.45 + 0.7x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + Y = -2.45 + 4 + 0.7x

Combine like terms: -4 + 4 = 0
0 + Y = -2.45 + 4 + 0.7x
Y = -2.45 + 4 + 0.7x

Combine like terms: -2.45 + 4 = 1.55
Y = 1.55 + 0.7x

Simplifying
Y = 1.55 + 0.7x

See similar equations:

| -6(-2x-2)=108 | | 3s+-5=-11 | | x-4x=6x+18 | | -3x+9=5x-71 | | 3(1+2x)=-6x+87 | | 5x-7=9+1 | | -2x+4x-33=9 | | Y-3.5=0.7(x-4) | | -4x+3=3-6x | | -4X-6Y+2Z=-2 | | n2+5=15 | | f(-1)=-3x | | -4(5m+20)=-400 | | 12-6z=2x+15 | | 7x+19=21 | | 6X+9Y-3Z=3 | | 3(3)(-3)-8(2)-3= | | -z^4+17z^2-16=0 | | 8c-71=12c-72-4c | | 3(-3+2x)=3x+3 | | 7(-2x-4)=-168 | | -(-2)+2(2.1)-(-2)= | | 51x-.83x^2=0 | | 2X+3Y-2=1 | | x^2*x=2 | | 3g+5wheng=4 | | 4y-5=-2x-31 | | 5X+Y-3Z=1 | | 55XY-3Z=1 | | z2+1=9 | | 4(-2)-3(-3)+2(2)= | | 3x+18+2=5x-4 |

Equations solver categories